Mortality burden of the 2009‐10 influenza pandemic in the United States: improving the timeliness of influenza severity estimates using inpatient mortality records. Issue 5 (19th February 2013) - Charu, Vivek; Simonsen, Lone; Lustig, Roger; Steiner, Claudia; Viboud, Cécile
Abstract : Background: Delays in the release of national vital statistics hinder timely assessment of influenza severity, especially during pandemics. Inpatient mortality records could provide timelier estimates of influenza‐associated mortality. Methods: We compiled weekly age‐specific deaths for various causes from US State Inpatient Databases (1990–2010) and national vital statistics (1990–2009). We calculated influenza‐attributable excess deaths by season based on Poisson regression models driven by indicators of respiratory virus activity, seasonality, and temporal trends. Results: Extrapolations of excess mortality from inpatient data fell within 11% and 17% of vital statistics estimates for pandemic and seasonal influenza, respectively, with high year‐to‐year correlation (Spearman's rho = 0·87–0·90, P  < 0·001, n  = 19). We attribute 14 800 excess respiratory and cardiac deaths (95% CI: 10 000–19 650) to pandemic influenza activity during April 2009–April 2010, 79% of which occurred in people under 65 years. Conclusions: Modeling inpatient mortality records provides useful estimates of influenza severity in advance of national vital statistics release, capturing both the magnitude and the age distribution of pandemic and epidemic deaths. We provide the first age‐ and cause‐specific estimates of the 2009 pandemic mortality burden using traditional 'excess mortality' methods, confirming the unusual burden of this virus in young populations. Our inpatient‐based approach could help monitor mortality trends in other infectious diseases.